Determinant Analysis of Salesperson's Performance at PT. Prima Zirang Utama Semarang - Widiartanto Widiartanto; Wahyu Hidayat (Universitas Diponegoro, 2020)
The purpose of this research is to test empirically the effect of salesperson behavior, sales activity planning, and performance orientation on salesperson performance at PT. Prima Zirang Utama Semarang. The research method used is the survey method, namely research that takes a sample from a population and uses a questionnaire as the main data collection tool. The type of research used is explanatory research. The samples studied were all salespeople at PT. Prima Zirang Utama Semarang, totaling 36 people. The result of this research is that there is a positive and significant influence between the salesperson's behavior, sales activity planning, and performance orientation on the salesperson's performance. This can be seen from the significant value in the ANOVA recapitulation of 0.026 indicating a value smaller than 0.05. This means that the regression model is feasible to predict the effect of salesperson behavior variables, sales activity planning, and performance orientation on salesperson performance variables.